Association between Cataract and Keratinocytic Skin Cancers or Melanoma: Speculating on the Common Role of Sun and Ultraviolet Radiation Exposures. (3rd September 2017) - Varssano, David; Friedman, Mira; Goldstein, Michaella; Bar-Sela, Shai; Sella, Tal; Shalev, Varda; Chodick, Gabriel
ABSTRACT: Purpose : Cataract and sun-related skin conditions are proxies to lifetime UV exposure. We examined the association between them using real-world data from an unselected Israeli population. Methods : Computerized data was obtained from an Israeli health maintenance organization regarding cases of sun-related skin pathologies and cataract diagnosed between 2006 and 2011 in 686, 260 members aged 40 or above. Results : Sun-related skin disorders were found in 9.3% of the study population, more commonly among the elderly, and those who reside in areas of higher socioeconomic status. Cataract was diagnosed in 13.1% of the study population, with highest prevalence (47%) among squamous cell carcinoma patients, who were the oldest group. Multivariable analysis adjusting for age, sex, residential district, birth region, smoking, and chronic comorbidities showed no statistically significant association between melanoma and cataract (OR = 1.06; 95% CI: 0.91–1.22). Basal cell carcinoma, squamous cell carcinomas, and actinic keratosis were associated with increased likelihood of prevalent cataract with adjusted odds ratios (95% CI) of 1.14 (1.08–1.20), 1.11 (1.01–1.19), and 1.16 (1.13–1.19), respectively. When stratified by gender, the association between actinic keratosis and cataract was stronger in women than in men, particularly in patients under 65 years. Conclusions : The association between the prevalence of skin cancers and the prevalence of cataract enhances the conclusion that cataract is related to UVR exposure.